Effects of litter input on soil aggregation and aggregate carbon turnover differ among three subtropical forests in southeastern China - Hu, Ya-Lin; Zheng, Zhi-Heng; Qin, Chu-Qiao; Leuzinger, Sebastian (Frontiers in Plant Science, 2025)
Background and aimsLitter input plays important roles in controlling soil aggregation and aggregate carbon (C) content. However, the effects of litter input on soil aggregate C turnover in different forest types remain unclear.MethodsWe examined the changes of aggregate mass proportion, and the litter-derived and native C content among soil aggregates after three years of aboveground and root litter input, using 13C isotope tracing in a natural forest, a Chinese fir (Cunninghamia lanceolate) plantation, and a masson pine (Pinus massoniana) plantation in southeastern China.ResultsBelowground root litter rather than aboveground litter input enhanced soil aggregation. Litter input increased total C content across all aggregates, and the effects were no different between aboveground litter and belowground root litter input except for the >2 mm fraction. Belowground root litter input led to less native C content across three forest types. However, belowground root litter input resulted in more formation of litter-derived C than aboveground litter input under masson pine plantations, but not for both natural forest and Chinese fire plantation, suggesting a different effect of litter input on the litter-derived C formation among forest types. In addition, forest type affected soil aggregation and aggregate C turnover, and the differences in litter quantity and litter C:N ratio can explain the changes in soil aggregation and aggregate C turnover among forest types.ConclusionOur results imply that belowground root litter input plays a more important role in controlling soil aggregation and aggregate C turnover than aboveground litter, and the impact on newly litter-derived C formation depends on forest type.